2015
DOI: 10.2174/1874834101508010038
|View full text |Cite
|
Sign up to set email alerts
|

Transverse Vibration Analysis of the Riser in Deep Water

Abstract: With high international oil price, the exhaustion of onshore resources and declination of oil and gas production in shallow sea, deep water has become the important succeeding area of worldwide oil and gas. During deepwater oil and gas development, riser must be used to isolate seawater, circulate drilling fluid, and compensate the heaving movements of the string and so on. However, with the operating water depth increasing, the loads of waves and ocean currents on the riser become more complex, leading to ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A considerable number of experiment studies and numerical simulations [4] - [14] for VIV under the uniform flow have been performed so far. However, currents are not uniform, but sheared.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable number of experiment studies and numerical simulations [4] - [14] for VIV under the uniform flow have been performed so far. However, currents are not uniform, but sheared.…”
Section: Introductionmentioning
confidence: 99%
“…The rod string dynamics in petroleum engineering had been studied extensively by many experts and scholars: the longitudinal vibration of sucker rod [13,14], the transverse vibration of traditional pressure bar [15,16] and moving beam [17,18], the transverse forced vibration of riser under tension [19][20][21], the transverse vibration and collision problems for wellbore under fluctuating pressure [22][23][24][25]. However, the research on the transverse vibration triggered by the buckling deformation excitation seems to have not been discovered so far.…”
Section: Introductionmentioning
confidence: 99%
“…Connaire et al (2015) used quasi-rotations and the NewtoneRaphson method for riser analysis and showed that the approach provided advantages for subsea riser sections. Li et al (2015) analyzed the transverse vibration of the riser and indicated that the largest transverse displacement was found in the upper section of the riser. Major et al (2015) studied the influence of drilling string rotation on the dynamic response of drilling risers and demonstrated that the drill string rotation reduced the natural frequency and increased the amplitude of the vibration of the drilling riser.…”
Section: Introductionmentioning
confidence: 99%